Analisa Penggunaan Besi Profil Siku sebagai Bahan Alternatif Pengganti Kayu pada Konstruksi Keramba Jaring Apung - Ferdinandus Sangur; Grasiano Warakano Lailossa (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2022)
During this period, wood has been widely used as Floating Net Cage (FNC) construction material. However, wood is often damaged due to the shear forces and bending moment. Therefore, it is necessary to look for an alternative material to replace it. This study aims to analyze the angle of steel as a substitute alternative of wood on the FNC construction. The research was conducted through two aspects of approach, the first is the technical aspects of construction (the buoyant force, shear forces, and bending moment) and the second aspect is the economic aspect (the costs of FNC). Research shows buoyancy due to changes mass of wooden construction = 10.263,77 kg and angles steel = 10.299,26 kg and to a slide and bending moment: for timber style sliding/shear forces = 121,06 kg and the bending moment = 452,39 kg.m, steel and angles the sliding = 116,62 kg and bending moment = 442,40 kg.m. Based on the economic aspect, the cost of construction FNC, IDR 1.550.000, the angles of steel cheaper than the cost of construction with wood IDR 2.120.000. This result showed that the angles steel, based on the technical and the economic aspect, can be used as an alternative material for substitute of wood in FNC.